Germs up close - Levine, Sara (Veterinarian) (Millbrook Press, 2021)
"Have you ever seen a germ up close? Really, really up close? Micrographs and illustrations combine with accessible text to introduce readers to viruses, bacteria, protozoa, and fungi-including COVID-19-that can make people sick"--